Covid-19 Adaptive Tourism Attraction: Tourism Resilience Through Chse Certification For Visiting Decision - Dwi Pratiwi Wulandari; Violintikha Harmawan; Yuke Permata Lisna; Sari Mustika; Indah Mustika (UNIVED Press, 2024)
CHSE (Clean, Health, Safety, and Environment) certification is implemented by the Indonesian government to restore tourism conditions post-pandemic. The research aim is to analyze tourists' visiting decisions to visit COVID-19 adaptive tourist attractions after the implementation of the CHSE certification policy as a strategy to restore tourism conditions post-pandemic. The descriptive research was carried out with a causal-associative quantitative approach using 100 respondents. The result revealed that: (1) The implementation of CHSE in COVID-19 is in the quite good category with a percentage of 50%. (2) Visiting decisions are in the quite good category with a percentage of 37.8%. (3) CHSE as a strategy to restore tourism conditions has an impact of 13.4% on visiting decisions. So, it is concluded that tourists decide to visit a COVID-19 adaptive tourist attraction, not solely because the tourist attraction has been CHSE certified. But 86.8% are influenced by other factors.